2015
DOI: 10.1021/acs.jpcc.5b01154
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of H2O Splitting and H2 Formation at the Cu(110)–Water Interface

Abstract: We used density functional theory to investigate the sequential oxidation of the (110) surface of fcc copper triggered by the dehydrogenation of molecularly adsorbed water-the reactions studied did not involve any oxygen besides that present in the water molecule. According to the obtained Gibbs free energies, the formation of half a monolayer of HO and the corresponding amount of hydrogen gas is spontaneous (∆ r G • <0) starting from a monolayer of adsorbed water at Cu(110). The subsequent dehydrogenation ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 99 publications
10
30
0
Order By: Relevance
“…Lower symmetry is often connected with decreased stability of the correspondent surface films when compared with higher symmetry structures . Recent DFT investigations have shown that for Cu(110), even though the dissociation products of H 2 O bind weaker to the surface than those originating from H 2 S, the former form higher symmetry structures than the H 2 S counterparts ,,. Because sulfide films are less protective than films of oxide – as shown in a combined DFT‐SEM‐EDX study – a connection is often made between the extent of the mismatch between the structures of the substrate‐adsorbate layer and the stability of the surface products .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower symmetry is often connected with decreased stability of the correspondent surface films when compared with higher symmetry structures . Recent DFT investigations have shown that for Cu(110), even though the dissociation products of H 2 O bind weaker to the surface than those originating from H 2 S, the former form higher symmetry structures than the H 2 S counterparts ,,. Because sulfide films are less protective than films of oxide – as shown in a combined DFT‐SEM‐EDX study – a connection is often made between the extent of the mismatch between the structures of the substrate‐adsorbate layer and the stability of the surface products .…”
Section: Introductionmentioning
confidence: 99%
“…[11] Recent DFT investigations have shown that for Cu(110), even though the dissociation products of H 2 O bind weaker to the surface than those originating from H 2 S, the former form higher symmetry structures than the H 2 S counterparts. [14,16,17] Because sulfide films are less protective than films of oxide [18] -as shown in a combined DFT-SEM-EDX study -a connection is often made between the extent of the mismatch between the structures of the substrate-adsorbate layer and the stability of the surface products. [13] For Cu surfaces, the origin of the more extensive reconstruction driven by sulfur species when compared to the O counterparts, lays largely in the strength of the bonding with the surface, because S binds considerably stronger than O by % 0.4 to 0.6 eV, as demonstrated by DFT computations and UPS spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, as highlighted by the authors of the cited study, the kinetics and energetics of such a process are dependent on the type of surface—the crystallographic plane—as well as the presence of surface defects. In aqueous media, R2 is expected to be slower—and have an energy barrier—due to the presence of surface defects and solvation effects as well as the hindering that these pose to the encounters between surface H-atoms when compared to the solid-gas interface38. The energy barrier for R3 corresponds to the transfer of an H-atom from solution into bulk Cu.…”
Section: Discussionmentioning
confidence: 99%
“…The background samples consist of non-irradiated copper exposed to water for the same period of time as that of the irradiated samples. The background samples are necessary because copper has some amount of hydrogen from the manufacturing and even without the influence of ionizing radiation copper can induce the formation of minute amounts of H 2 (g) when exposed to water3738. This is because water can adsorb dissociatively on some copper surfaces and this process leads to the formation of both HO • and H • , the latter is a precursor of H 2 38.…”
Section: Introductionmentioning
confidence: 99%
“…For some applications, where the system is driven out of equilibrium, the knowledge of the structure and properties of stable as well as metastable compounds is necessary for for understanding, predicting, and controlling the behavior of copper. Although Cu 2 O and CuOH have been detected as products of copper corrosion under anoxic conditions 4,[6][7][8] , some circumstances of such corrosion behavior are still unclear 9,10 .…”
Section: Introductionmentioning
confidence: 99%